A rare variant of mullerian agenesis: a case report and review of the literature - Shriya Devendra Tayade; Nadia Mehdi; Rajani Dube; Vaishnavi Bose; Ashna Ameer; Zainabsadat Tabatabaei Hakim; Arnaud Wattiez (Journal of Medical Case Reports, 2024)
Abstract Introduction Menstruation is a developmental milestone and usually marks healthy and normal pubertal changes in females. Menarche refers to the onset of first menstruation in a female. The causes of primary amenorrhea include outflow tract abnormalities, resistant endometrium, primary ovarian insufficiency, and disorders of the hypothalamus, pituitary, or other endocrine glands. A rare variant of mullerian agenesis, which warrants an individualized approach to management, is presented here. Case report We present here the case of a 25-year-old Indian female with pain in the lower abdomen and primary amenorrhea. After a thorough history, clinical examination, imaging, and diagnostic laparoscopy, two small uteri, a blind upper half vagina, bilateral polycystic ovaries, and a blind transverse connection between the two uteri—a horseshoe band cervix—were detected, which confirmed the diagnosis of mullerian agenesis. There was evidence of adenomyosis in the mullerian duct element. This is a rare form of Müllerian abnormality with an unusual presentation. Conclusion Mullerian agenesis is the most common cause of primary amenorrhea with well-developed secondary sexual characteristics. There are various forms of mullerian agenesis. Most of the cases are managed by a multidisciplinary team. Rare variants warrant an individualized approach to management.